8x-3(3x+2)=

Simple and best practice solution for 8x-3(3x+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-3(3x+2)= equation:


Simplifying
8x + -3(3x + 2) = 0

Reorder the terms:
8x + -3(2 + 3x) = 0
8x + (2 * -3 + 3x * -3) = 0
8x + (-6 + -9x) = 0

Reorder the terms:
-6 + 8x + -9x = 0

Combine like terms: 8x + -9x = -1x
-6 + -1x = 0

Solving
-6 + -1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -1x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -1x = 0 + 6
-1x = 0 + 6

Combine like terms: 0 + 6 = 6
-1x = 6

Divide each side by '-1'.
x = -6

Simplifying
x = -6

See similar equations:

| 2x^2+22=0 | | 7(x-7)+16= | | 92=6(x-70)+50 | | 2x^4-x^3-x^2=0 | | x^2+y^2-4x-6y+4=0 | | 2y-2=6y+2 | | -2(-y-2)-x= | | 6x^2+7x-3=y | | .2+.2x=.4 | | 12x^2+82x-14=0 | | 3(1+d)+-5=3d+-2 | | 3x^2-35x-5=0 | | 6x-1=6x+12 | | 2yw+4y-yw-3y= | | -4w+1+w-6= | | kv-kv^2=q | | (6y+4)-(2+5y)=8 | | -20+X=51 | | 12x+3x-12=0 | | 3x^2-42x+147+9=0 | | 16m^2-8m-3=0 | | 5.9+x=4.1 | | 10=27-2(-3-2w) | | A^5+4-6a^3=0 | | 5z+5h+n=q | | x^3-3x^2-2x+6=0 | | A^5+4+2a=0 | | 11=29-8(-1-5w) | | 11x-32=7x+4 | | 6y-(y-8)=-20 | | 246(98x)=x | | -3(-6w-v)-4(4v-3w)= |

Equations solver categories